2004
DOI: 10.1111/j.1365-2648.2004.03129.x
|View full text |Cite
|
Sign up to set email alerts
|

Practice nurses’ intentions to use clinical guidelines

Abstract: Future trials of interventions to increase practice nurses' adherence to clinical guidelines could attempt to address the elements identified in this study as important factors. Further studies are required to examine the utility of the TPB in predicting practice nurses' behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 35 publications
8
79
1
1
Order By: Relevance
“…The TPB is a psychological elaboration of the behaviours of rational actors. Limited applications had suggested that the TPB was useful in understanding provider behaviour [57]. A preliminary framework was developed and then discussed in a series of iterative meetings between the researchers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TPB is a psychological elaboration of the behaviours of rational actors. Limited applications had suggested that the TPB was useful in understanding provider behaviour [57]. A preliminary framework was developed and then discussed in a series of iterative meetings between the researchers.…”
Section: Discussionmentioning
confidence: 99%
“…The interviewees valued practice nurses' roles in guideline implementation while running mini-clinics for chronic diseases [47,57]. Nurses informed GPs of new guidelines.…”
Section: Theme Iv: Influential People In Implementationmentioning
confidence: 99%
“…These includeV but are not limited toVthe consistency of attitudes and behavior toward organ donation (Siegel, Navarro, Tan, & Hyde, 2014), adherence to clinical guidelines (Kortteisto, Kaila, Komulainen, Mäntyranta, & Rissanen, 2010;Puffer & Rashidian, 2004), health literacy (Pleasant, McKinney, & Rikard, 2011), and medication adherence (Sutton, 2011). As one example, a study with intensive care nurses showed that, when nurses' knowledge and attitudes related to bowel management for critically ill patients were improved, nurses were more likely to perform the bowel management practices dictated by the protocol (Knowles et al, 2015).…”
Section: Overviewmentioning
confidence: 97%
“…To be consistent with previous research into how the TPB predicts healthcare provider behavior, attitude was measured using two scales: attitude toward the behavior and behavioral beliefs [14,11]. The outcome in this analysis was the intention to deliver advice to quit cigarette smoking in clinical rotations.…”
Section: Instrument Developmentmentioning
confidence: 97%